Pelatihan Pendamping Proses Produk Halal - Ulfah, Nurul; Widiastuti, Hanifah; Thohari, Ahmad Hamim; Zaenuddin, Muhammad; Fajrin, Aulia; Purba, Adi Syahputra; Batubara, Ninda Hardina; Stefani, Windy; Hidayat, Imam; Wirawan, Adhitomo (Politeknik Negeri Batam, 2023)
Halal products are products that are starting to be looked at by the market today. One of the goals of the Indonesian government, under BPJPH, in 2024 it is hoped that products, especially food and beverages in Indonesia, will already have halal certificates so that they can increase the attractiveness of pariwasata for Muslims around the world if they visit Indonesia. Based on the new legislation in 2014, namely law no. 33 of 2014 concerning Halal Product Guarantee, the halal certification process is carried out in synergy by various parties, one of which is the halal product guarantee organizing body (BPJPH). Halal product process assistance is a process of verifying and validating halal statements by business actors (self-declare). This activity serves to assist micro and small business actors in meeting product halal requirements. The purpose of this community service is to find out the level of understanding of prospective halal product process assistants in Batam City, service activities are carried out with 3 stages, namely surveys, socialization and training activities and the last stage is evaluation and reports. This activity is supported by BPJPH and Bank Indonesia as additional sponsors for activities to be carried out offline and online.